Inverse Domination on a Middle graph of some cycle related graphs (Cuestiones de Fisioterapia, 2024)
Let G be non-trivial graph. A dominating set for a graph G is a subset D of its vertices,such that any vertex of G is in D, or has a neighbor in D. The set S⊂ V(G)- D such that Sis a dominating set of G, then S is called an inverse dominating set with respect to D. Theminimum cardinality of an inverse dominating set is called an inverse dominating numberand is denoted by γ^' (G). In this paper we find inverse domination number on Middlegraph of some graphs.